Evaluation of high-dose aspirin elimination in the treatment of Kawasaki disease in the incidence of coronary artery aneurysm - Farima Sanati; Mohammadmehdi Bagheri; Shahryar Eslami; Ali Khalooei (Wolters Kluwer Medknow Publications, 2021)
Background: Standard first-step therapy for Kawasaki disease consists of Intravenous immunoglobulin and high dose Aspirin (80-100 mg/kg/day). The standard dose of Intravenous immunoglobulin (2gr/kg) is strongly effective in reducing the risk of coronary arteries abnormalities. So, the proper dose and efficacy of Aspirin to decrease the risk of coronary arteries abnormalities is a controversial issue. In this study, it is tried to assess the result of eliminating high-dose Aspirin in the treatment of the acute phase of Kawasaki and observe the incidence rate of coronary arteries abnormalities when only Intravenous immunoglobulin was administered.Methods: This study is a prospective randomized, open-label, blinded end-points clinical trial performed in Afzalipour hospital in Kerman University of Medical Sciences from September 2017 to September 2018 in 62 patients with typical and atypical Kawasaki disease. The study group received Intravenous immunoglobulin (2 g/kg) and the control group get the same dose of Intravenous immunoglobulin plus Aspirin with the dose of 80-100 mg/Kg/day until they were afebrile for 48 hours. Afterward, both groups received a daily single dose (3-5 mg/kg) of Aspirin for six weeks. Echocardiography was done after two weeks, six weeks, and six months. Internal the diameter of the left and right main coronary arteries was measured and then the corresponding Z-score was calculated.Results: In the study group, coronary arteries abnormalities decreased from 38.7% in the 2nd week to 16.1% in the 6th month. In the control group, it declined from 54.8% to 22.6%. There was no statistically significant difference between the groups in term of frequency abnormal coronary arteries abnormality at the study period (P=0.151).Conclusions: We concluded that high dose Aspirin does not have a significant role in preventing coronary arteries abnormalities in Kawasaki disease and giving standard 2 gr/kg/day Intravenous immunoglobulin without high-dose Aspirin in acute-phases therapy does not increase the risk of coronary arteries abnormality.